Malignant Transformation of Oral Submucous Fibrosis: Risk Factors and Biomarkers – A Comprehensive Review (Academia Journal of Medicine, 2026)
Oral submucous fibrosis (OSMF) is a chronic, progressive, potentially malignant disorder  predominantly associated with areca nut consumption. It is characterized by fibrosis of  the oral mucosa, leading to restricted mouth opening and increased risk of malignant  transformation into oral squamous cell carcinoma (OSCC). The rate of malignant  transformation varies widely, emphasizing the need for early identification of high-risk  individuals. This review aims to summarize the key risk factors and emerging biomarkers  associated with malignant transformation in OSMF. Major risk factors include prolonged  areca nut use, tobacco consumption, genetic susceptibility, nutritional deficiencies, and  chronic inflammation. Recent advances have highlighted the role of molecular biomarkers  such as p53, Ki-67, cyclin D1, and various salivary and serum markers in predicting malignant  potential. Understanding these factors is crucial for early diagnosis, risk stratification, and  timely intervention. The integration of clinical assessment with molecular diagnostics may  improve patient outcomes and reduce the burden of oral cancer.
Keywords: Oral submucous fibrosis; Malignant transformation; Oral squamous cell carcinoma; Areca nut; Biomarkers